"Sensor based sorting systems for minerals-State-of-the-art technology for higher product qualities and higher profits in the mining industry" - Michael Klug (Instituto de Ingenieros de Minas del Peru, 2017)
"In the past the optical sorting in the mining sector has not enjoyed an outstanding and very celebrated position in the industry because of insufficient computer–, sensor– and valve-technologies. Due to the fast development processes in the last years, companies nowadays can offer a high efficient system to the industry. Sensor based sorting is already an outstanding and proven technique and has become an important alternative to either extensive process steps or the widely spread handpicking.The increasing costs for the latter results in manual sorting of more coarse material. "